Study of Synoptic and dynamic the occurrence of blocking on the snow in February 2014 in Iran - فاطمه درگاهیان; بهلول علیجانی (مخاطرات محیط طبیعی, 2017)
Blocking can be effective in Occurrence of damaging climatic hazards. In order to investigate the role of blocking in the event of heavy snowfall and persistent 31January 31 to5 February 2014, maps Average air pressure at sea level, 850, 500, 300, layer thickness map between 1000 and 500, the position of zero degree isotherm at ground level, U-Wind, V-Wind, Omega (Vertical Velocity, relative humidity, temperature and potential temperature are analyzed. The results showed that Iran is located influence strong and deep right, blocking trough of Omega has a very strong ridges width of 70 degrees north. With the falling of cold air from higher latitudes along with strong high pressure center located in the Caspian Sea with 1050 hpa pressure, With plentiful moisture and temperature conditions especially at the level of 500 and 850 hpa, Regarding the nature of blocking and quasi-stationary conditions continue for 6 days, most parts of Iran was accompanied with snow and some areas due to their position and other conditions were exposed heavy, sustained snow. Investigation the dynamic components showed that in adulthood blocking these components reached its peak and led to continuous heavy snow in most parts of the country. Identification blocking systems that led to heavy snowfall prediction using maps and issue timely early warnings can help planners and decision makers affected areas to prepare for and prevent further damage.